Docking Studies, Synthesis and Evaluation of Anticancer Activity of 4H-Chromene Derivatives - Kumar, Piyush; Rawat, Pinki (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The present study involves to design, synthesis and evaluate the anticancer activity of 4H-chromene derivatives (PKB 1-10) on human breast cancer MCF-7 cell line. Materials and Methods: 4H-chromene derivatives (PKB 1-10) were designed by docking, in silico ADME and predicted toxicity studies. These designed compounds were then synthesized by acid catalyzed Michael Addition of phenols to benzylidene oxobutanoates. These compounds were characterized by 1H NMR, 13C NMR, FTIR and melting point. Then all synthesized compounds were tested for anticancer activity on MCF-7 cell line. Results: Compounds PKB-4 and PKB-10 showed better docking scores than standard drug, Adriamycin. In silico ADME and toxicity studies were also found significant for most of the compounds. The majority of the compounds displayed promising to potent anticancer activity on MCF-7 cell line. Conclusion: It may be concluded that most of the compounds showed significant docking and in silico ADME and toxicity profiles. Compounds have excellent anticancer potential and could be considered as novel anticancer agents for more investigation.
Keywords: Anticancer; 4H-chromenes; Docking; MCF-7 cell line; Toxicity